2007
DOI: 10.1103/physrevlett.98.236601
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and Correlations in Graphene

Abstract: Graphene is described at low energy by a massless Dirac equation whose eigenstates have definite chirality. We show that the tendency of Coulomb interactions in lightly doped graphene to favor states with larger net chirality leads to suppressed spin and charge susceptibilities. Our conclusions are based on an evaluation of graphene's exchange and random-phase-approximation correlation energies. The suppression is a consequence of the quasiparticle chirality switch which enhances quasiparticle velocities near … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
302
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(308 citation statements)
references
References 31 publications
5
302
1
Order By: Relevance
“…[104]). When one dopes the system away from the neutrality point, screening kicks in and the electron fluid in singlelayer graphene behaves as a Fermi liquid, albeit with a number of intriguing twists [12,105,106].…”
Section: Long-range Interactionsmentioning
confidence: 99%
“…[104]). When one dopes the system away from the neutrality point, screening kicks in and the electron fluid in singlelayer graphene behaves as a Fermi liquid, albeit with a number of intriguing twists [12,105,106].…”
Section: Long-range Interactionsmentioning
confidence: 99%
“…The measured frequency and weight enhancement of the in-phase optical plasmon mode follows, respectively, the square-root and the linear dependence on the number of graphene sheets in GMLS, i.e. √ N and N , which differs from the weak inlayer density dependence, n 1/4 and n 1/2 , obtained respectively for the plasmon fre- quency and its weight both in single- [25][26][27][28][29] and doublelayer [39][40][41][42] graphene structures. This effect is strikingly different from that in conventional two-dimensional systems in semiconductors where, if exchange and correlations effects 59 are neglected, the in-phase plasmon mode in a symmetrically balanced double-layer system behaves similarly to that in an individual layer with the doubled density.…”
Section: Introductionmentioning
confidence: 99%
“…The recent theoretical calculations of the bubble diagram of the Lindhard polarization function, Π 0 (ω, q), in monolayer graphene [25][26][27] show that for an arbitrary bosonic frequency, ω, and momentum, q, its dependence on the carrier density, n, is weaker, Π 0 (ω, q) ∝ √ n, than the dependence Π 0 (ω, q) ∝ n in conventional two dimensional electron systems with a parabolic energy dispersion. As a direct consequence, the frequency of charge density waves, ω p , in a quantum system of chiral massless Dirac fermions shows a unique carrier density scaling, ω p ∝ n 1/4 , which is in contrast with conventional two-dimensional plasma ω p ∝ n 1/2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic wavefunctions in graphene systems are often described using a pseudospin language in which the spinors specify wavefunction components on different sublattices. Although the properties of graphene 2DES's can often be successfully described using an effective noninteracting electron model, studies of electron-electron interactions effects have revealed some qualitative differences compared to ordinary 2DES's 4,5 that are related to these sublattice pseudospin degrees-of-freedom.…”
Section: Introductionmentioning
confidence: 99%